Grain Quality of Rice (Oryza sativa L.) ‘Menthik Wangi’ of Organic Farming Yields - Dwi Umi Siswanti; Maryani Maryani; Fitria Yulia Rachmawati; Aprida Niken; Rega Virgiyana Agustin; Niken Wulansari (HAYATI Journal of Biosciences, 2021)
Organic rice is believed to have better nutrition than conventional rice. Not all organic rice grain is consumed. Most of the organic cultivation yields will be used as seed. Viability test is one of the quality test of rice seed. Viability is seed vitality that can be shown as a physiological and biochemical phenomenon. Seed that have high vigor will achieve high productivity levels as well. The aims of this research was to analyze the quality of rice cultivar Menthik Wangi of organic farming yields. The quality of rice seeds was tested by measuring the viability of seed and crude fat content. The test results demonstrate the viability of the grain has a 100% germination, 100% growth potential maximum, 99.33%, simultaneity grew, 97.33% vigor index, T50 2.33, and seed moisture content 10.67%. The fat content was conducted by soxhlet method and analyzed by T-test. The results showed that organic rice has a higher fat content (0.53%) than non-organic rice (0.24%). It can be concluded that rice seed cultivar Menthik Wangi of organic farming has a higher viability and fat content than the non-organic rice grain.